Implementasi Pemberian Layanan Bantuan Hukum Secara Cuma-Cuma Oleh Posbantuan Hukum pada Perkara Pidana di Pengadilan Negeri Gedong Tataan (Studi Kasus di Posbakum Adin Lampung) - Baharudin Baharudin; Iqbal Alin Perdana (Universitas Batanghari Jambi, 2021)
In legal cases, namely legal cases experienced by someone, there are often problems with one's inability to be able to hire a lawyer to handle the trial process in court, in fact a suspect still has his rights in a trial, one of which is to get assistance before the law of course for defend the rights of the suspect, in cases like this if someone does not have the ability to hire a lawyer POSBAKUM or the Legal Aid Post plays an important role in helping a suspect in providing legal services in the form of consultation, legal advice and the preparation of legal documents that are really needed by a suspect based on statutory regulations, in defending a suspect the trial is carried out for free, that way every suspect from being able or not entitled to get legal assistance